Three-dimensional quantification of protoporphyrin IX in photodynamic therapy using SFDI/DFT: A pilot experimental validation - Mai Dan; Weijie Song; Meihui Liu; Yaru Zhang; Feng Gao (Journal of Innovative Optical Health Sciences, 2022)
Photodynamic therapy (PDT) dosimetry, including light dose, photosensitizer dose and tissue oxygen, has been a research focus in PDT. In this work, we present a three-dimensional (3D) quantification of protoporphyrin IX (PpIX) using combined spatial frequency domain imaging (SFDI) and diffuse fluorescence tomography (DFT). The SFDI maps both the distributions of tissue absorption and scattering properties at three wavelengths and accordingly provides the optical background for DFT and extracts the tissue oxygenation for assessing the therapeutic outcomes, while DFT dynamically monitors the 3D distribution of PpIX dose from measured fluorescence signals for the procedure optimization. A pilot in vivo application in tumor nude models showed that the proposed SFDI/DFT is able to dynamically trace changes in the PpIX concentration and tissue oxygen during the treatment, rendering it a potentially powerful tool for PDT to improve clinical efficacy.